2015
DOI: 10.11600/1692715x.13118040414
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar Subjetivo y Calidad de Vida en la Infancia en Chile

Abstract: El artículo presenta los resultados de la Encuesta Internacional sobre Bienestar Subjetivo infantil (ISCWeB), aplicada en Chile en el año 2012. El cuestionario fue aplicado a una muestra de 2.734 niños y niñas, de 8, 10 y 12 años, residentes de las tres principales zonas urbanas del país. Los resultados dan cuenta de una alta satisfacción con la vida, existiendo diferencias al considerar las variables nivel socioeconómico y sexo, así como también distintos aspectos. Los ámbitos mejor evaluados corresponden a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
2
15
0
3
Order By: Relevance
“…For example, Chen et al (2019) found that boys and girls obtained higher scores than adolescents. Similarly, Petito and Cummins (2000) found that well-being decreased with age, and other studies have confirmed that as adolescence progresses, satisfaction with life decreases (Suldo and Huebner, 2004;Tomyn and Cummins, 2011;Casas et al, 2012;Oyanedel et al, 2015). Gender differences also seem to be present during adolescence.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, Chen et al (2019) found that boys and girls obtained higher scores than adolescents. Similarly, Petito and Cummins (2000) found that well-being decreased with age, and other studies have confirmed that as adolescence progresses, satisfaction with life decreases (Suldo and Huebner, 2004;Tomyn and Cummins, 2011;Casas et al, 2012;Oyanedel et al, 2015). Gender differences also seem to be present during adolescence.…”
Section: Introductionmentioning
confidence: 75%
“…This relationship was higher in countries with less access to these material resources (Algeria, Uganda, and South Africa) and lower in countries with better access conditions (South Korea, England, and Spain). In Chile, research has shown that lower SES is related to lower happiness, using a single-item measure of happiness (Oyanedel et al, 2015). In contrast, Kwan (2008) found that life satisfaction among adolescents from the same geographical context is independent of their economic situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El Estudio Nacional de Calidad de Vida relacionada con la salud (CVRS) de adolescentes chilenos (Sepúlveda et al, 2013), con una muestra de 7.910 jóvenes entre 10-18 años, encontró alarmantes porcentajes de ausentismo asociados a una baja calidad de vida, y entre otros resultados, las mujeres presentan mayores puntajes en la mayoría de las dimensiones evaluadas. Otro estudio, la Encuesta Internacional sobre Bienestar Subjetivo infantil (ISCWeB) (Oyanedel, Alfaro y Mella, 2015); aplicada el año 2012 con una muestra de 2.734 niños y niñas de entre 8 y 12 años, mostró que más del 70% de la población infantil y adolescente se declara satisfecha con su vida en todas las edades consideradas, reportando mayor satisfacción en ámbitos de salud, bienes materiales y familia; y menos satisfacción en ámbitos de barrio y colegio. Además, la SV es menor en los niños de 8 años en relación a sus pares de 10 y 12 años.…”
Section: La Satisfacción Vital Infantilunclassified
“…Therefore, it is necessary to work on practices that contribute to the reduction of secondary victimization in child and adolescent witnesses or victims of crimes, adopting measures that protect the guarantees that avoid confrontation with the aggressor at the time of testifying 14 , having a conditioned environment, in which the process is also carried out by specialized professionals in order to avoid the testimony repetition 15 , contributing to the exercise of the child's right to express his/her opinion without coercion 16,17 , which affects his/her subjective well-being and capacities to exercise his/her rights in an actively 18 .…”
Section: Introductionmentioning
confidence: 99%